Private Agri-food Standards:Contestation, Hybridity and the Politics of Standards - Bain, Carmen; Ransom, Elizabeth; Higgins, Vaughan (The International Journal of Sociology of Agriculture and Food, 2013)
The articles in this first issue of the IJSAF Private Agri-food Standards special issue expand on the body of literature that has focused on the enactment and standardization of standards. In particular, this issue focuses on the contestation, hybridity and the politics of standards. Specifically, several articles investigate and complicate the divide between so-called public versus private standards. While private standards have correctly been identified as coinciding with the rise of neo-liberalism and an audit culture (Campbell and Le Heron, 2007; Higgins et al., 2008), it is somewhat ‘premature to assume that all non-governmental standards have the same political, social and cultural impacts’ (Kimura, this issue, emphasis in original). The diversity of the operations and outcomes of private standards becomes particularly salient when focusing on different locations and contexts.